Inside Cover: Exploring the Structural Space of the Galectin‐1–Ligand Interaction (ChemBioChem 15/2017). (19th July 2017) - Bertleff‐Zieschang, Nadja; Bechold, Julian; Grimm, Clemens; Reutlinger, Michael; Schneider, Petra; Schneider, Gisbert; Seibel, Jürgen
Abstract : The inside cover picture shows the complex of the tumor‐associated protein Galectin‐1 and a N ‐acetyllactosamine (Lac N Ac)‐based inhibitor. We wanted to introduce new binding interactions into our new lectin inhibitors by probing the complex glycan structures presented on the protein′s surface. We expanded the Lac N Ac scaffold in a stepwise manner by using a multifunctional mimetic; this led to ligands that share a highly conserved binding mode. More information can be found in the communication by C. Grimm, J. Seibel et al. onpage 1477 in Issue 15, 2017 (DOI:10.1002/cbic.201700251 ).